C++/CLI in Action - Sivakumar, Nishant (Manning Publications, 2007)
C++/CLI in Action is a practical guide that will help you breathe new life into your legacy C++ programs. The book begins with a concise C++/CLI tutorial. It then quickly moves to the key themes of native/managed code interop and mixed-mode programming. You'll learn to take advantage of GUI frameworks like Windows Forms and WPF while keeping your native C++ business logic. The book also covers methods for accessing C# or VB.NET components and libraries.